Sinomenine hydrochloride exerts antitumor outcome in ovarian cancer cells by inhibition of long non-coding RNA HOST2 expression - Yuting Xu; Tao Jiang; Changhe Wang; Fei Wang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Background Accumulating evidence displays that sinomenine hydrochloride (SH) are utilised to treat a variety of cancers. Nevertheless, the influences of SH on ovarian cancer stay blurry. We endeavoured to uncover the antitumor effects of SH on ovarian cancer and underlying mechanism(s).Methods Human ovarian epithelial cell line (HOEpiC), Caov3 and SKOV3 cells were administrated with SH and/or transfection with pc-long non-coding RNA (lncRNA) human ovarian cancer-specific transcript 2 (HOST2), then cell viability, cell cycle and apoptosis and the related-proteins were respectively inspected by MTT, flow cytometry, and Western blot. In addition, expression of HOST2 was investigated by real-time PCR. Kaplan-Meier manner with the log-rank investigation was achieved to calculate overall survival.Results SH remarkably repressed cell viability, evoked apoptosis and induced cell cycle arrest in G0/G1. Moreover, SH statistically decreased HOST2 expression in Caov3 and SKOV3 cells. Overexpression of HOST2 significantly reversed the effects of SH on Caov3 cell viability, cell cycle and apoptosis. Clinical findings confirmed that HOST2 was profoundly higher expressed in ovarian cancer tissues and cells, and HOST2 predicated unfavourable prognosis of ovarian cancer individuals.Conclusion Our findings recommended that SH exerted the antitumor effect in ovarian cancer cells by hindering expression of HOST2.